A study on gender differences in academic achievement at University Malaysia Sabah (UMS) / Jessita Joseph - Joseph, Jessita (2009)
Educational statistics and worldwide media have reported a gender gap in academic achievement, with boys falling behind girls with regard to grades, high school graduation, and college enrollment and retention. This study examines the existence of genders gaps in education and the factors that lead into the lower performance of student. This study consist the reviewed from the student of Conservation Biology program in School of Science and Technology, UMS. 100 respondents were involved in this study which comes from Diploma, Bachelor, and Master and above level of student from that program. The findings shows that there is existence of gender differences in academic achievement and the factor, behaviors affected the student academic performance but not for the class environment.